2017
DOI: 10.1002/jts.22244
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress, Somatization, and Quality of Life Among Ivorian Refugees

Abstract: The present study examined the relationship between peritraumatic reactions, posttraumatic stress disorder (PTSD) symptoms, somatization, and quality of life (QoL) in a sample of refugees, two years after the 2011 Ivory Coast sociopolitical crisis. Participants were 101 Ivorian adult refugees (mean age = 31.61 years, SD = 7.84; 45.5% women) who completed several questionnaires relating to peritraumatic reactions, PTSD symptoms, somatization, and QoL. Most participants (86.1%) scored above the cutoff for probab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 42 publications
6
13
0
Order By: Relevance
“…The traumatic journey is constantly relived, even after the return, in the form of repetitive and pervasive memories provoking a feeling of distress and including images, thoughts or ideas in the form of recurring dreams of the traumatic experience, evoking the probable existence of post-traumatic stress, even months or years after the traffic. This hypothesis confirms the results of our previous work where even two years after the sociopolitical crisis in Ivory Coast, 86% of Ivorian refugees had symptoms of probable posttraumatic stress (Kounou et al, 2017). According to table 2, almost the majority of the children had gone to Nigeria.…”
Section: The Child and His Family On Returnsupporting
confidence: 90%
“…The traumatic journey is constantly relived, even after the return, in the form of repetitive and pervasive memories provoking a feeling of distress and including images, thoughts or ideas in the form of recurring dreams of the traumatic experience, evoking the probable existence of post-traumatic stress, even months or years after the traffic. This hypothesis confirms the results of our previous work where even two years after the sociopolitical crisis in Ivory Coast, 86% of Ivorian refugees had symptoms of probable posttraumatic stress (Kounou et al, 2017). According to table 2, almost the majority of the children had gone to Nigeria.…”
Section: The Child and His Family On Returnsupporting
confidence: 90%
“…The present evidence of somatization may be attributed to the traumatic events experienced by the participants. Kounou et al also found that somatization among refugees may be a consequence of their trauma experienced, suggesting that trauma-centered therapies target not only the usual clinical picture of PTSD or depression but also possible evidence of somatoform disorder [26]. In Arabic culture, especially among women, somatoform disorder is often presented as so-called heart excitement, since there are few other ways to express emotional distress [27] (p. 76).…”
Section: Complaintsmentioning
confidence: 99%
“…Nevertheless, measuring somatic symptoms and severity is important for the assessment, prevention and treatment of psychological trauma and common mental disorders following humanitarian crises [21] and has proven to be a valid construct across cultures [22]. When somatic distress has been examined in conflict-affected and displaced populations, it has been shown to limit daily functioning [23], reduce quality of life [24] and increase health service utilisation [25]. Thus, an improved understanding of this phenomenon in these populations is likely to be important for reducing individual suffering, increasing health service efficiency and closing the mental health treatment gap.…”
mentioning
confidence: 99%